CBS News - 60 Minutes
An episode of CBS News’ television program “60 Minutes” featuring: Ed Bradley’s report on racism and the miscarriages of justice in Tulia, Texas, U.S.; Lesley Stahl’s report on musical savant Rex Lewis Clack who was born blind and with brain damage, but is able to play songs on the piano after hearing them a single time; Mike Wallace’s investigation of eminent domain abuse in Lakewood, Ohio, where the officials are forcing people off their land, so private developers can build more expensive homes and offices that would generate more income to the city; Steve Kroft’s report on the political situation in the U.S., the approval rating of President George W. Bush., and the profile of the competing candidates for the next U.S. presidency; Morley Safer’s evening news.